The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1371/journal.pone.0235063
|View full text |Cite
|
Sign up to set email alerts
|

Performance of mid-upper arm circumference as a screening tool for identifying adolescents with overweight and obesity

Abstract: Background Adolescent overweight and obesity is a global public health problem, associated with an increased risk of metabolic syndrome. Recently, mid-upper arm circumference (MUAC) has been suggested as a screening tool to identify overweight and obesity among school-age children and early adolescents (5-14 years). However, little is known about the potential use of MUAC in the late adolescence period (15-19 years). Therefore, the present study aimed to evaluate the performance of MUAC to identify overweight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 27 publications
3
22
0
Order By: Relevance
“…Lower cut-offs for overweight of 27.7 and 27.9 cm were also identified for male and female adolescents (15-19 years) living in Addis Ababa, Ethiopia [38]; this suggests that MUAC could be influenced by factors such as age, and thus appropriate cut-offs for specific age groups such as adolescents and the elderly should be evaluated. Furthermore, MUAC itself can be considered a valuable additional and independent marker for assessing nutritional status, rather than just a simpler method and substitute of the BMI.…”
Section: Discussionmentioning
confidence: 93%
“…Lower cut-offs for overweight of 27.7 and 27.9 cm were also identified for male and female adolescents (15-19 years) living in Addis Ababa, Ethiopia [38]; this suggests that MUAC could be influenced by factors such as age, and thus appropriate cut-offs for specific age groups such as adolescents and the elderly should be evaluated. Furthermore, MUAC itself can be considered a valuable additional and independent marker for assessing nutritional status, rather than just a simpler method and substitute of the BMI.…”
Section: Discussionmentioning
confidence: 93%
“…Even though BMI is highly correlated with excess adiposity, it misclassifies a significant number of children and adolescents (9) . Except for one (20) , none of the included studies reported the time interval between performing the index test and reference standard. However, it is unlikely that any time delay between conducting the index test and the reference standard would introduce bias.…”
Section: Risk Of Bias and Publication Biasmentioning
confidence: 99%
“…The mid-upper arm circumference (MUAC) has been proposed as one such alternative to screen for overweight and obesity in children and adolescents (17)(18)(19)(20) . It is a simple measure commonly used to screen for undernutrition in infants and children aged 6-59 months (21) as well as thinness and severe thinness in adolescents (22,23) .The existing evidence of the usefulness of the MUAC against the BMI Z-score among children and adolescents is limited and unclear (17)(18)(19)(20)(24)(25)(26) . Therefore, this systematic review and meta-analysis aim to summarise the currently available evidence on the performance of MUAC to identify children and adolescents with overweight and obesity.…”
mentioning
confidence: 99%
“…DXA is in fact considered the gold standard to measure body composition [19][20][21]. Mid-upper arm circumference (MUAC) has shown potential as a low cost, convenient, and reliable alternative to BMI to identify overweight and obesity in all pediatric age groups [22,23]. When it comes to global relevance of MUAC, a study across 12 countries and the socioeconomic spectrum, including an SA country, stated that MUAC as a tool is accurate for identifying obesity in 9-11-year-old children across the 12 countries.…”
Section: Literature Reviewmentioning
confidence: 99%